Analisis Fenomena Female Genital Mutilation di Asia Tenggara melalui Perspektif Feminis Interseksional - Pohan, Nabila Yasmin; Zahra, Anya Azzura; Dero, Moosa; Umar, Muhammad Arsyady; Nuraeni, Nuraeni (Global and Policy Journal of International Relations, 2023)
This research provides an overview of the issue of Female Genital Mutilation (FGM) in Southeast Asia and its relation to the Sustainable Development Goals (SDGs). FGM is the harmful traditional practice of removing part or all of the external female genitalia that is often followed by disastrous health consequences for women. This issue is specially related to SDG Goal 5, which aims to achieve gender equality. In examining this issue, intersectionalist feminist theory provides a framework for understanding the root causes of FGM and developing effective strategies to deal with this practice, as well as analyzing and addressing how FGM perpetuates gender-based violence and discrimination against women, especially those belonging to multiple marginalized groups. In the case of FGM in Southeast Asia, the connection between intersectionality lies in practices that occur within certain cultural and religious communities and is deeply rooted in gender inequality and patriarchy. Therefore, an intersectional feminist approach to FGM can explore how gender, culture, and other social factors intersect to shape experiences of violence and oppression for women, as much as it can address the correct strategies to eradicate it and protect women.DOI: https://doi.org/10.33005/jgp.v11i01.3940